ADAPTATION OF FILM TITLES IN INTERCULTURAL COMMUNICATION - Василевська, Тетяна (SWorldJournal, 2026)
The article examines the problems and features of adapting film titles – in intercultural communication. The main attention is paid to how cultural differences, linguistic features and connotations affect the perception and translation of film titles. Ex